Identification of Xanthomonas vasicola (formerly X. campestris pv. musacearum), causative organism of banana xanthomonas wilt, in Tanzania, Kenya and Burundi - Carter, B.A.; Reeder, R.; Mgenzi, S.R; Mwangi, M.; Aritua, Valentine; Smith, J.; Beed, Fenton D.; Kinyua, Z.M.; Nakato, V.; Miller, S.; Mbaka, J.N.; Doyle, K.; et al. (Wiley, 2010)
Xanthomonas campestris pv. musacearum (Xcm) causes a disease onbanana (Musa spp.) and enset (Ensete spp.) known as banana xanthomonaswilt (BXW). Recent studies have shown that Xcm is a strain of X. vasicola(Aritua et al., 2008). However, the status of pathovars within thespecies remains unclear. Prior to its discovery in Uganda in October 2001,the disease had been limited to Ethiopia (first reported 1968). Since thenthe disease has spread to the Democratic Republic of Congo and Rwanda(observed in May 2004 and September 2005 respectively). BXW cancause high yield losses and is a high priority concern within the GreatLakes region. A comprehensive review of the pathogen and diseasewas recently published by Smith et al. (2008). Thus far, outbreaks inTanzania, Kenya and Burundi have only been referred to in symposiumproceedings and on various websites. These new records are thus officiallyreported here for the first time.In Tanzania, the disease was first reported in the Kagera region of northwest Tanzania, bordering Lake Victoria, Uganda, Rwanda and Burundi,in September 2005 (Mgenzi et al., 2006). Spread has continued, but not toother major banana growing areas. In Kenya, the disease was firstreported in September 2006 in the Teso District, of western Kenya,bordering Uganda (Anon, 2006). Spread has since been reported as slow.In Burundi the disease was first observed during October 2006 (Anon.,2006). The current status of BXW in Burundi is unclear with no recentsubstantiated reports.Bacterial cultures were isolated from diseased racemes from Tanzaniaand Burundi at CABI, UK and from Kenya at KARI (NARL). All cultureswere identified to species level at FERA by fatty acid profiling (MIDI system)and DNA analysis using X. vasicola specific primers (Aritua et al.,unpublished data) and partial sequencing of the gyrase B gene (Parkinsonet al., 2007). Koch’s postulates were fulfilled for all strains at FERA bystem inoculation of banana plants (height approximately 30 cm) with abacterial suspension (200 lL with ~107 cfu ⁄ mL) under controlled environmentalconditions (minimum temperature 27ºC). Identification ofXcm isolates from Burundi and Kenya was further supported by OhioState University and KARI, respectively, using X. vasicola specific primers(Lewis-Levy Miller, unpublished data) that have a different target site tothose of Aritua et al. (unpublished data).Reference cultures are held by the UK National Collection of PlantPathogenic Bacteria, Accession Nos. NCPPB 4392-5 (Tanzania), 4434(Kenya) and 4433 (Burundi).